PS 07-14 VASCULAR PROTEIN OXIDATION AND REDOX PROTEOMICS IN HYPERTENSION. (September 2016) - Tsiropoulou, Sofia; Montezano, Augusto; Scott, Alan; Burchmore, Richard J.; Touyz, Rhian M.
Abstract : Objective: Oxidative stress is implicated in hypertension (HTN) through redox-sensitive processes causing vascular damage. It remains unclear exactly how ROS cause vascular injury. We hypothesise that in HTN, increased ROS levels promote a shift of oxidative post-translational protein modifications from reversible into irreversible forms, leading to aberrant redox signalling and vascular injury. Design and Method: VSMCs from normotensive and hypertensive rats (WKY and SHRSP) were stimulated with AngII (10–7 M). Protein carbonylation was assessed by oxyblot. Protein tyrosine phosphatase (PTP)-oxidation was assessed by immunoblotting. Protein sulfenylation was detected using the DCP-Rho1 cell permeable, fluorescent probe. Differential gel electrophoresis (DiGE) and CyDye thiol labelling were employed for screening of reversibly oxidised proteome. Results: Irreversible protein carbonylation and PTP-hyperoxidation were increased in SHRSP compared to WKY (fold change (FC) = 1.29 and FC = 1.31, p < 0.05, respectively). AngII-stimulation induced PTP-hyperoxidation but not protein carbonylation in VSMCs from WKY rats (FC = 1.32 at 15 min, p < 0.05), with no alterations observed in SHRSP. On the contrary, reversible oxidation was reduced in SHRSP versus WKY, as demonstrated through thiol-proteome oxidation (13.6% (253 spots) decreased versus 6.7% (124 spots) increased oxidation), protein sulfenylation (FC = −1.78, p < 0.05) and PTP-oxidation (FC = −1.24, p < 0.05). AngII-stimulation tended to further decrease sulfenylation and PTP-oxidation levels in WKY. Proteomic data, filtered for FC > 2, detected 1777 spots with 377 (21%) being differentially oxidised between WKY and SHRSP. Candidate proteins exhibiting consistent changes across three replicates included β-actin (FC = 2.42), annexin A1 (−2.29), galectin-1 (1.83) and GAPDH (2.67). Conclusions: Our findings demonstrate that redox status in HTN is characterised by increased protein hyperoxidation and decreased levels of reversible oxidation. AngII is able to shift the balance between regulatory oxidation and hyperoxidation towards a hypertensive profile. Our findings identify differentially oxidised proteins in VSMCs in SHRSP vs WKY. These phenomena may be important in aberrant vascular signaling/function, contributing to oxidative vascular injury in HTN and associated target organ damage.